Code-Switching used by Putri Tanjung and Boy William in Ngobrol Sore Semaunya’s Episode 2 - Azyizah, Sitti; Nuryanti, Dewi (LingPoet: Journal of Linguistics and Literary Research, 2023)
This study wants to investigate the code-switching that occurred in the Podcast Ngobrol Sore Semaunya’s Podcast Episode 2. This study also aims to describe the types of code-switching, the factors causing the code-switching, and the function of code-switching that occurred in the Podcast Ngobrol Sore Semaunya Episode 2. This study used qualitative descriptive research. The object of this research is a data containing code-switching in speech events on the Podcast Ngobrol Sore Semaunya Episode 2. The result showed three results. The first type of code-switching that occurs according to Stockwell (2007) there are, 1) tag-switching, 2) intra-sentential switching, 3) inter-sentential switching. Second, the reason that causes code-switching according to Hoffman (1991), there are 1) talking about particular topic, 2) quoting somebody else, 3) express solidarity, 4) interjection, 5) repetition used for clarification, 6) intention of clarifying the speech content for the interlocutor and, 7) expressing group identity. The last is the code-switching function according to Gumperz (1982), there are 1) quotation, 2) addressee specification, 3) interjection or sentence filler, 4) reiteration, 5) message qualification, and 6) objectification.